2010
DOI: 10.3109/03008207.2010.528566
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin resides in mouse skin and upregulates hyaluronan synthesis in dermal fibroblasts

Abstract: Adipose tissue is a hormonally active tissue that produces adipokines that influence the activity of other tissues. Adiponectin is an adipocyte-specific adipokine involved in systemic metabolism. We detected the expression of adiponectin receptors (AdipoR1 and AdipoR2) mRNA in cultured dermal fibroblasts. The full-length adiponectin (fAd), but not the globular adiponectin (gAd), increased hyaluronan (HA) production and upregulated HA synthase (HAS) 2 mRNA expression. AdipoR1 and AdipoR2 mRNAs were also express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
(56 reference statements)
1
28
0
2
Order By: Relevance
“…In addition, adiponectin is a hair growth stimulator that increases the secretion of growth factors from dermal papillae cells and hair matrix keratinocyte proliferation [5]. Moreover, adiponectin induces proliferation of dermal fibroblasts and upregulation of collagen production [6] and promotes hyaluronan synthesis with increased hyaluronan synthase [7, 8]. The age-dependent decreasing pattern of adiponectin in skin suggests the possibility that adiponectin plays a role in skin aging [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adiponectin is a hair growth stimulator that increases the secretion of growth factors from dermal papillae cells and hair matrix keratinocyte proliferation [5]. Moreover, adiponectin induces proliferation of dermal fibroblasts and upregulation of collagen production [6] and promotes hyaluronan synthesis with increased hyaluronan synthase [7, 8]. The age-dependent decreasing pattern of adiponectin in skin suggests the possibility that adiponectin plays a role in skin aging [8].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this theory, adiponectin can regulate the expression of several cytokines that activate the immune system (Takahashi et al 2010) and can modulate keratinocyte proliferation and migration through the ERK signaling pathway (Shibata et al 2012). Moreover, adiponectin receptors are expressed in cultured dermal cells (Akazawa et al 2011) and adiponectin can promote hair growth in vitro (Won et al 2012), hinting at the possibility that adiponectin derived from dermal adipocytes might also regulate hair follicle biology.…”
Section: Potential Additional Roles Of Adipocytes In the Skinmentioning
confidence: 99%
“…A study has recently reported the presence of adiponectin in mouse skin . Although it is possible that adiponectin may move from the bloodstream to the skin, sebocytes in the sebaceous gland can produce adiponectin .…”
mentioning
confidence: 99%